Targeting lung cancer through inhibition of checkpoint kinases - Syljuåsen, Randi G.; Hasvold, Grete; Hauge, Sissel; Helland, Åslaug (Frontiers in Genetics, 2015)
Inhibitors of checkpoint kinases ATR, Chk1 and Wee1 are currently being tested in preclinical and clinical trials. Here, we review the basic principles behind the use of such inhibitors as anticancer agents, and particularly discuss their potential for treatment of lung cancer. As lung cancer is one of the most deadly cancers, new treatment strategies are highly needed. We discuss how checkpoint kinase inhibition in principle can lead to selective killing of lung cancer cells while sparing the surrounding normal tissues. Several features of lung cancer may potentially be exploited for targeting through inhibition of checkpoint kinases, including mutated p53, low ERCC1 levels, amplified Myc, tumor hypoxia and presence of lung cancer stem cells. Synergistic effects have also been reported between inhibitors of ATR/Chk1/Wee1 and conventional lung cancer treatments, such as gemcitabine, cisplatin or radiation. Altogether, inhibitors of ATR, Chk1 and Wee1 are emerging as new cancer treatment agents, likely to be useful in lung cancer treatment. However, as lung tumors are very diverse, the inhibitors are unlikely to be effective in all patients, and more work is needed to determine how such inhibitors can be utilized in the most optimal ways.